2018
DOI: 10.1093/ons/opy022
|View full text |Cite|
|
Sign up to set email alerts
|

Stereoelectroencephalography-Guided Laser Ablations in Patients With Neocortical Pharmacoresistant Focal Epilepsy: Concept and Operative Technique

Abstract: The preliminary experience with the described method shows the feasibility of a unique combination of the SEEG methodology with laser thermocoagulation in patients with neocortical MRI-negative pharmacoresistant focal epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Once clinicians have sufficiently formed an SOZ hypothesis based on the iEEG data they have collected, and deem that surgery will not affect eloquent regions, then they proceed with surgery. The types of procedures can be broadly classified as a resection, or laser ablation [147, 128, 148, 149].…”
Section: Supplementary Materials and Methodsmentioning
confidence: 99%
“…Once clinicians have sufficiently formed an SOZ hypothesis based on the iEEG data they have collected, and deem that surgery will not affect eloquent regions, then they proceed with surgery. The types of procedures can be broadly classified as a resection, or laser ablation [147, 128, 148, 149].…”
Section: Supplementary Materials and Methodsmentioning
confidence: 99%
“…MRI-guidance and MR thermography combined with dedicated software allow precise, real-time monitoring of the procedure and direct visual feedback regarding the threedimensional (3D) distribution of the induced thermal tissue damage, thus providing an opportunity to avoid injury to functionally important brain structures [8,9]. LITT also offers the ability to produce lesions of various volumes and shapes by modifying the laser probe position along the planned trajectory [10].…”
Section: Laser Interstitial Thermal Therapymentioning
confidence: 99%
“…Today, stereotactic ablative techniques are used for limited conditions: arteriovenous and cavernous malformations, HHs, mesial temporal lobe sclerosis and, to a lesser extent, complex and deep focal cortical dysplasias, nodular periventricular heterotopias, tuberous sclerosis [139] and subependymal giant cell astrocytomas [140]. Favorable reports exist also for stereoelectroencephalography-guided surgery of neocortical nonlesional epilepsy [10].…”
Section: Drug-resistant Epilepsymentioning
confidence: 99%
“…Laser ablation with MR-guided laser interstitial thermal therapy (MR-g-LITT) is another minimally-invasive technique in which a fiber-optic laser applicator is stereotactically inserted, and ablation is performed while acquiring real-time thermal MRI sequences [27,45,61,62]. At some centers, SEEG electrodes are used to identify ablation targets [82]. Favorable outcomes from SEEG followed by MR-g-LITT for children with MRE have been described [18], although one study reported a relatively high rate of transient functional deficits (7/24 procedures, 29.2%) [78].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%